Exploring the role and efforts of Islamic organizations in reviving Islamic faith among the Hui Muslim communities in early 20th century in China - Mai Jianjun; Fatmir Shehu (Ar-Raniry: International Journal of Islamic Studies, 2021)
This paper seeks to explore the role and efforts of Islamic organizations in reviving Islamic faith among the Hui Muslim communities in early 20th century in China. The study shows how the Hui Islamic organizations led by the Hui Muslim religious leaders and intellectuals actively engaged in various types of programs and activities to revive and promote Islamic faith among the Hui Muslim communities in China. It brings important insights into the history of Islamic revival movement in China. The focus of discussion in this study is on: Background of the Islamic revival movement and the Hui Islamic organizations. The historical, descriptive and analytical methods are used in the entire research. The study finds out that the Hui Muslims during Republic of China period responded proactively to the social and political changes in the society to advance the cause of Islamic revival. Two strategies are identified, i.e. adapting to the environment and reviving and promoting Islamic faith through Islamic organizations led by religious leaders and intellectuals. This could provide some insights to the Hui Muslims to cope with current situations in China.